The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1038/sj.onc.1202650
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in breast cancer cells MDA-MB-231 by genistein

Abstract: Breast cancer is the most common cancer among American women, whereas Asian women, who consume a traditional diet high in soy products, have a relatively low incidence. Genistein is a prominent iso¯avonoid in soy products and has been proposed as the agent responsible for lowering the rate of breast cancer in Asian women. We investigated the e ects of genistein on cell growth and apoptosis-related gene expression in breast cancer cells MDA-MB-231. We found upregulation of Bax and p21 WAF1 expressions and downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
200
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 289 publications
(222 citation statements)
references
References 43 publications
(43 reference statements)
16
200
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25] Previous studies reported from our laboratory have shown that genistein regulates genes that are related in controlling cell proliferation, cell cycle, apoptosis, oncogenesis, transcription regulation, angiogenesis, and cancer cell invasion and metastasis. [26][27][28][29][30] We have also shown that genistein inhibits NF-jB activation, which is partly mediated via Akt signaling pathway. 31 We therefore hypothesize that genistein may alter the sensitivity of pancreatic cancer cells to conventional therapies by overcoming de novo as well as acquired chemoresistance due to inactivation of NF-jB during chemotherapy.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Previous studies reported from our laboratory have shown that genistein regulates genes that are related in controlling cell proliferation, cell cycle, apoptosis, oncogenesis, transcription regulation, angiogenesis, and cancer cell invasion and metastasis. [26][27][28][29][30] We have also shown that genistein inhibits NF-jB activation, which is partly mediated via Akt signaling pathway. 31 We therefore hypothesize that genistein may alter the sensitivity of pancreatic cancer cells to conventional therapies by overcoming de novo as well as acquired chemoresistance due to inactivation of NF-jB during chemotherapy.…”
mentioning
confidence: 99%
“…3,4 It has been found that genistein can inhibit the growth of various cancer cell lines both in vitro and in vivo. [5][6][7][8][9][10] Our previous studies also showed that genistein can induce apoptosis and inhibit NF-jB activation in pancreatic cancer cells. 8,9,11 NF-jB plays important roles in the control of cell growth, differentiation, apoptosis and inflammation.…”
mentioning
confidence: 99%
“…Furthermore, the p53 and p21 WAF1 tumor suppressor genes are also known to be involved in apoptotic processes, and we have detected the expression of p53 gene in MDA-MB-231 breast cancer cells, which are ER-negative and harbor mutant p53. Although the treatment of these cells with genistein downregulated the expression of the dysfunctional p53, the expression of p21 WAF1 was induced within 24 h [37]. These results suggest that the induction of p21 WAF1 and apoptosis by genistein is functionally operated through a p53-independent pathway.…”
Section: Effects On the Induction Of Apoptosismentioning
confidence: 53%